The effect of white matter integrity on functional outcome in central pontine demyelination - Lee, Kyoung Bo (J Phys Ther Sci, 2019)
[Purpose] Central pontine demyelination is a common osmotic demyelination syndrome. Typically, central pontine demyelination shows high signal intensity with demyelination in the mid-pons. Despite severe imaging findings, patients usually recover. This study investigated the integrity of the corticospinal tract (CST) and corticoreticular pathway (CRP) in patients at 12 months after the onset of central pontine demyelination. [Participants and Methods] This retrospective cross-sectional observational study assessed two patients with central pontine demyelination, who were ultimately able to walk without using an aid or orthosis and to use both hands but with mild residual symptoms. All participants underwent diffusion tensor imaging (DTI) at 12 months after onset. [Results] Both patients had mild ataxia at 12 months after onset. The integrity of the CST was restored in both cases, while the integrity of the CRP recovered partially. [Conclusion] The integrity of the CST and CRP at 12 months after the onset of central pontine demyelination was similar in both cases as well as the recovery status of the hand function and ambulation. These results may be useful in planning therapy for patients with central pontine demyelination.